RHEUMATOID ARTHRITIS: THE PROBLEMS OF REMISSION AND THERAPY RESISTANCE - E. L. Nasonov; Yu. A. Olyunin; A. M. Lila (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is an immunoinflammatory (autoimmune) rheumatic disease of unknown etiology, which is characterized by chronic erosive arthritis and systemic visceral organ damage that results in early disability and shorter patient survival. Despite RA treatment advances associated with the design of novel drugs and the improvement of treatment strategies to achieve remission in many patients, there are still many theoretical and clinical problems concerning both the definition of the concept of remission, its characteristics and types and approaches to the optimum policy of symptomatic and pathogenetic drug therapy at different stages of the disease, the use of which will be able to rapidly induce and maintain remission in the long-term. Further investigations are needed to study the nature of heterogeneity of pathogenetic mechanisms of RA and approaches to early diagnosis, to improve methods for monitoring disease activity and biomarkers for the efficiency of and resistance to therapy and, finally, to develop differentiation therapy, including those related to a search for new therapeutic targets.